2020
DOI: 10.3389/fmars.2020.609156
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Evolution of Mesoscale Anticyclones in the Lee of Crete

Abstract: Motivated by the recurrent formation of mesoscale anticyclones in the southeast of Crete, we investigated with a high resolution model the response of the ocean to orographic wind jets driven by the Cretean mountain range. As shown in the dynamical process study of Ioannou et al. (2020) which uses a simplified shallow-water model, we confirm here, using the CROCO (Coastal and Regional Ocean COmmunity) model, that the main oceanic response to the Etesian wind forcing is the formation of mesoscale anticyclones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Notice that in the Eastern Mediterranean Sea, Ioannou et al. (2020a, 2020b) also reported intense and recurrent mesoscale anticyclones in the lee of Crete forced by an orographic wind jet produced by the channeling and deflection of the Etesian winds by the island, showing similarities with the orographic effect of the Pyrenees as highlighted here. The authors confirmed that these winds were necessary but not sufficient to form the eddies and suggested that this mechanism had to be reinforced by some other baroclinic process.…”
Section: Discussionsupporting
confidence: 66%
“…Notice that in the Eastern Mediterranean Sea, Ioannou et al. (2020a, 2020b) also reported intense and recurrent mesoscale anticyclones in the lee of Crete forced by an orographic wind jet produced by the channeling and deflection of the Etesian winds by the island, showing similarities with the orographic effect of the Pyrenees as highlighted here. The authors confirmed that these winds were necessary but not sufficient to form the eddies and suggested that this mechanism had to be reinforced by some other baroclinic process.…”
Section: Discussionsupporting
confidence: 66%
“…In addition to this statistical validation against altimetric data, Ioannou et al. (2020) showed that the numerical solution CROCO‐MED60v40‐15‐16 exhibits realistic mesoscale features even after 3 years of free simulation: some of these features are even very commensurable with observations (density anomaly, main dynamical parameters, and tracking of a mesoscale eddy). More generally the simulated hydrology has been systematically compared to the CORA v5.2 data set and to SST fields from Meteosat SEVIRI imager.…”
Section: High‐resolution Model Of the Mediterranean Seamentioning
confidence: 89%
“…However, due to the high spatial resolution of the numerical model, small scale patterns such as the North Ligurian current and the Rhodes Gyre current appear to be much stronger in CROCO-MED60v40. Besides this statistical validation against altimetric data Ioannou et al (2020) showed that the numerical solution CROCO-MED60v40-15-16 exhibits realistic mesoscale features even after 3 years of free simulation : some of these features are even very commensurable with observations (density anomaly, main dynamical parameters and tracking of a mesoscale eddy). More generally the simulated hydrology has been systematically compared to the CORA v5.2 dataset and to SST fields from Meteosat SEVIRI imager.…”
Section: High-resolution Model Of the Mediteranean Seamentioning
confidence: 75%